Guidelines for diagnosis and treatment of depression in older adults: A report from the Japanese Society of mood disorders. Issue 6 (6th April 2022) - Baba, Hajime; Kito, Shinsuke; Nukariya, Kazutaka; Takeshima, Minoru; Fujise, Noboru; Iga, Junichi; Oshibuchi, Hidehiro; Kawano, Masahiko; Kimura, Mahiko; Mizukami, Katsuyoshi; Mimura, Masaru; ,
Abstract : The Committee for Treatment Guidelines of Mood Disorders, Japanese Society of Mood Disorders, published a Japanese guideline for the treatment of late‐life depression in 2020. Based on that guideline, the present guideline was developed and revised to incorporate the suggestions of global experts and the latest published evidence. In the diagnosis of late‐life depression, it is important to carefully differentiate it from bipolar disorders, depressive states caused by physical and organic brain disease, drug effects, and dementia, and to determine the comorbidity between late‐life depression and dementia. It is necessary to fully understand the clinical characteristics and psychosocial background of late‐life depression, evaluate the patient's condition, and provide basic interventions based on these factors. Problem‐solving therapy, reminiscence therapy/life review therapy, and behavioral activation therapy, and other forms of psychotherapy can reduce depressive symptoms. In terms of pharmacotherapy, newer antidepressants or non‐tricyclic antidepressants are recommended for late‐life depression, and it is recommended that the efficacy of least the minimal effective dosage should first be determined. Switching antidepressants and aripiprazole augmentation can be used to treatment‐resistant therapy. Electroconvulsive therapy and repetitive transcranial magnetic stimulation have demonstrated usefulness for late‐life depression. Exercise therapy, high‐intensity light therapy, and diet therapy also show some effectiveness and are useful for late‐life depression. Continuation therapy should be maintained for at least 1 year after remission.